The effect of institutional performance and service quality on brand image through student satisfaction: A literature review - Lusiani, Lusiani; Vilicia Erwandi, Geofanny; Esti Susanti, Christina (Technium Sustainability, 2025)
This study aims to fill the gap in the literature by conducting a comprehensive analysis of institutional performance and service quality and discussing their role in university brand image through student satisfaction. Universities should pay attention to dominant factors such as student satisfaction and loyalty to improve the positive image of the institution. Better quality of higher education will improve the image of the institution.